Universal health coverage in relation to antenatal care services and its correlates - Aarati Sharma; Manish Kumar Goel; Damodar Bachani; Sanjeev Kumar Rasania (Wolters Kluwer Medknow Publications, 2018)
Introduction: Universal health coverage (UHC) means all people receiving the health services they need, of sufficient quality to be effective while at the same time ensuring that the use of these services does not expose the user to financial hardship. So, we did this study to assess the extent of UHC in relation to antenatal care services in Palam area of Delhi. Objectives: 1) To study the extent of coverage of antenatal services in Palam area of Delhi. 2) To assess the correlates of coverage of antenatal services among mothers. Material and methods: study type- a community based descriptive study was conducted between September 2015 to March 2017, among 250 mothers who delivered during the year 2015. A pretested, self-designed, semi-structured interview schedule and health records was used to collect information. Data was analysed using software - statistical package for social sciences (SPSS) version 20. Results: Out of 250 study participants, complete coverage of antenatal care services was seen in only 28.8% women. Literacy and presence of complication in previous pregnancy found to have statistically significant correlation with the extent of coverage of antenatal services. Conclusion: Women need to be educated about their health needs and services available to them, in order to increase the demand of maternal health services and improve utilization of available services.